Technology acceptance of augmented reality to attitude and self-efficacy in learning English - Ryani Yulian; Yuniarti Yuniarti; Noor Azli Bin Affendy Lee (UPT Bahasa Universitas Tanjungpura, 2022)
This study examined the effects of the technology acceptance of augmented reality on attitude and self-efficacy in learning English and modelled the direct and indirect effects. It employed non-experimental, analytic survey research with structural equation modelling. Two hundred and fifty-seven participants completed the survey questionnaire. Data analysis used SmartPLS to examine the outer loading, validity and reliability, R square, path coefficients, specific indirect effects, total effects, and model fit. Structural equation modelling (SEM) showed that perceived usefulness has no significant effect on attitude and self-efficacy, while perceived ease of use has a significant effect on attitude but no significant effect on self-efficacy. Perceived enjoyment has a positive correlation with attitude and self-efficacy. This study provides empirical facts that support and contradict previous relevant studies on the technology acceptance on attitude and self-efficacy in using augmented reality technology for language learning. The results of the study also contribute ideas on how technology can be anchored not only from technological but also from cognitive and affective perspectives as well.